NAOB: På vei mot en nasjonalordbok for bokmålet: Nyordprosjektet ”2014 nyord i 2014” - Nilstun, Carina (Nordiske Studier i Leksikografi, 2018)
This article reports from the campaign ”2014 neologisms in 2014”, con-ducted by the editors of The Norwegian Academy’s Dictionary (NAOB), as a step towards publishing a national dictionary for the Norwegian variety bokmål. The Academy’s dictionary will be published on <naob.no> in 2017. The campaign aimed to involve our future users, inviting them to search for neologisms with us. In a weekly feature in a popular radio program throughout the whole 2014, a winner was announced, and by the end of the year, our goal was reached: 2014 neologisms were collected, lexicographically prepared and published.